Penyajian Data, Ukuran Tendensi Sentral dan Letak - Nurhaswinda, Nurhaswinda; Fitriyah , Jihan Arika; Khairunnisa3, Siti (LANCAH: Jurnal Inovasi dan Tren, 2025)
Data presentation is a crucial first step in statistical analysis, aiming to facilitate the understanding of the information contained within the data. This article discusses various methods of data presentation and introduces measures of central tendency used to describe the central value in data distribution. The measures of central tendency covered in this article include mean, median, and mode. Additionally, this article also discusses the concept of location in statistics, which relates to the position or distribution of data within a particular group. With a deep understanding of data presentation, measures of central tendency, and location, statistical analysis can be conducted more accurately, providing a clearer picture of the data being analyzed. The presentation of measures of central tendency and location is an important aspect of statistical analysis used to describe the distribution and position of data within a dataset. Measures of central tendency, such as the mean, median, and mode, offer insights into the central value or the most frequently occurring value in the data. Meanwhile, measures of location, such as quartiles, percentiles, and interquartile range, help to understand the spread of data and the position of specific values within the overall data context. This study aims to explain how to present and apply these measures in various types of data and how they can be used to make more informed and accurate decisions in statistical analysis. By understanding the presentation of central tendency and location measures, it is expected that a deeper understanding of the patterns and characteristics of the analyzed data can be achieved. Furthermore, this study will also address the limitations and challenges in using these measures and how to choose the appropriate measure based on the characteristics of the data at hand.